Answer:
(x+4)(x-4)(x+4i)(x-4i) (answer D)
Explanation:
We can re-write the original binomial as a difference of squares noticing that
and that
![x^4=(x^2)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8vjhbtba1vg40a7gc7o00eeqgxmy94v9cq.png)
Then we have:
![x^4-256=(x^2)^2-16^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p7wjuhtba0wr2alg5l3bt3zyx503rsjlk9.png)
Then we can factor this out using the difference of squares factor form:
![(x^2)^2-16^2=(x^2+16)(x^2-16)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9rndi86a75ixxurnykc4tudfj9ufx81ls4.png)
Now,
, is itself a difference of squares which we can factor out further:
![x^2-16=x^2-4^2=(x+4)(x-4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/60w7zegywxphguvia0kyyarw6izxuwemqr.png)
And we can also solve for the binomial:
:
![x^2+16=0\\x^2=-16\\x=+/-√(-16) \\x=+/-i\,√(16) \\x=+/-4\,i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hmgdz4vl8ftvslio6c89py9evgneo4jmbj.png)
then we can write
![(x^2+16)=(x+4i)(x-4i)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fbomywehnuxdzemaia3wo95fj9zzfnv7f8.png)
Therefore, the final factor form of the original binomial is the product of all factors we found:
![(x+4)(x-4)(x+4i)(x-4i)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lc5hi41od7jc3bltn220gajowlp4s7d2jk.png)